2021
DOI: 10.1177/2515690x211068837
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia lactiflora Extracts Prevent Inflammatory Responses of Human Macrophages Stimulated with Charcoal Pyrolysis Smoke

Abstract: Artemisia lactiflora, a Chinese-origin plant, has been reported to have unique phytochemicals responsible for its medicinal properties. The growth of the agricultural industry emits air pollution, which has adverse effects on health. There are limited scientific reports on the biological activities of A. lactiflora. Studies on its activities and mechanisms may provide insight into its use in medicinal purposes to treat those health problems and conditions. In this study, leaves of A. lactiflora were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The residual salt fraction, in contrast, had the highest polarity with the lowest cytotoxicity (highest LC 50 ). Our toxicity result was correlated with previous study, which showed that toxicity of A. lactiflora extract and fractions depended on the polarity of solvents used in extraction and fractionation (Kooltheat et al, 2021). We found that LC 50 of A. lactiflora extract on cardiomyoblasts was approximately 10-times higher than previous toxicity study on human macrophages (Kooltheat et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The residual salt fraction, in contrast, had the highest polarity with the lowest cytotoxicity (highest LC 50 ). Our toxicity result was correlated with previous study, which showed that toxicity of A. lactiflora extract and fractions depended on the polarity of solvents used in extraction and fractionation (Kooltheat et al, 2021). We found that LC 50 of A. lactiflora extract on cardiomyoblasts was approximately 10-times higher than previous toxicity study on human macrophages (Kooltheat et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Higher polar phenolics were further fractionated with n-butanol, separated from the residual salt fraction. The extract and fractions were dried through evaporation, weighed, and stored in a desiccator (Kooltheat et al, 2021;Kooltheat et al, 2023).…”
Section: Preparation Extraction and Fractionation Of Artemisia Lactif...mentioning
confidence: 99%
See 2 more Smart Citations
“…Different polarity of solvents was used to fractionate the extracts: diethyl ether for the fractionation of non-polar compounds; chloroform for the fractionation of non-phenolic polar compounds; diethyl ether for the fractionation of low-polar polyphenolic compounds; butanol for the fractionation of high polar polyphenolic compounds. 17 , 39 , 40 Our result was implied that the butanol solvent was the most appropriate in extracting the phenolic and flavonoid compounds of the P. cerasoides flower, the same as the methanol solvent (a high polarity solvent) in extracting the phenolic and flavonoid compounds of stem barks and leaves. It was also stated that all extracts from P. cerasiodes contained flavonoid and phenolic contents.…”
Section: Discussionmentioning
confidence: 69%